If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = 56 Reorder the terms: -10 + 3x = 56 Solving -10 + 3x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3x = 56 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 56 + 10 3x = 56 + 10 Combine like terms: 56 + 10 = 66 3x = 66 Divide each side by '3'. x = 22 Simplifying x = 22
| 2=x+x^2 | | 1/9*-8-9 | | N+5+7=8n-8n+4 | | 4=9.5 | | a^3-b^6= | | 9ln(x)=-1 | | (9x+24)+(6x+6)= | | -3x-2y+12=0 | | (4x+17)+28=6x | | 5+n=8n+5-4n | | 1.4z-5=3.7 | | 9(k-10)=k | | (x+3)2=36 | | 7p-1=-15 | | 5.3x-8.1=23.7 | | 900x=400+100x | | F(x)=3x+9Findf(2c-4) | | -8n+7n=-n | | 14x/15=7/30 | | 288*.30=x | | 3v-1+2+16=5+5v+4 | | X*.30=86.50 | | 3x-20=2x+2 | | 2(2x+1)-x=11 | | 12=2/3x-4 | | 2(5-3x)=3(4x+1) | | 12+5b=-2b-5b | | -top-4=to | | F(1)=3x^2-7 | | 3x+6y+1=10 | | 9f^2+f=0 | | 9u=3 |